2012
DOI: 10.1177/1756283x12456895
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation for the treatment of radiation proctitis: a case report and review of literature

Abstract: Radiation proctitis is a frequent complication of pelvic radiation for cancer. This condition can present acutely within several weeks of radiation, or chronically many months or years after radiation, leading to rectal bleeding and transfusion-dependent anemia. Various medical and endoscopic therapies have been described to treat this condition; however, some patients fail to respond to the current standard therapies. Here we present a case of refractory radiation proctitis, with suboptimal response to other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…Various series have reported efficacy ranging from 66% to 100% for neodymium/yttrium aluminum garnet treatments (101,110). Taylor et al (111) reported on 23 patients treated with the potassium titanyl phosphate laser and followed for a median of 29 months and found that 65% experienced symptomatic improvement, although 2 patients developed rectal ulcers.…”
Section: Laser and Heater And Bipolar Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various series have reported efficacy ranging from 66% to 100% for neodymium/yttrium aluminum garnet treatments (101,110). Taylor et al (111) reported on 23 patients treated with the potassium titanyl phosphate laser and followed for a median of 29 months and found that 65% experienced symptomatic improvement, although 2 patients developed rectal ulcers.…”
Section: Laser and Heater And Bipolar Probesmentioning
confidence: 99%
“…Radiofrequency ablation generates thermal ablation at a superficial depth (0.5e1 mm), potentially making it even less invasive than APC (110). In the first report of radiofrequency ablation for RP, Zhou et al (117) treated 3 patients with chronic bleeding, achieving hemostasis in one to two sessions for all 3 patients.…”
Section: Radiofrequency Ablation and Cryoablationmentioning
confidence: 99%
“…Initial observations of its success in RP came from case reports and small series. [37,38] More recently, a retrospective study looked at 17 patients with chronic RP (heavy bleeding with clots or bleeding requiring transfusion) who underwent RFA treatment. After a median of two RFA sessions and at 6 months of follow-up, significant improvement was seen in symptoms (bleeding and tenesmus) and mean hemoglobin concentration, and 69% of patients who previously required transfusions no longer needed them.…”
Section: Evolving Techniques In Endoscopic Hemostasismentioning
confidence: 99%
“…APC is considered the preferred therapy, with an overall success rate as high as 80% [1, 3]. However, it has been associated with serious complications (e.g., perforation, fistulas, and strictures), and the efficacy is limited in patients with active bleeding, extensive disease and distally located lesions (anorectal junction) [2, 4].…”
mentioning
confidence: 99%
“…However, it has been associated with serious complications (e.g., perforation, fistulas, and strictures), and the efficacy is limited in patients with active bleeding, extensive disease and distally located lesions (anorectal junction) [2, 4]. RFA covers a broader area, has a superficial depth of ablation (0.5–1 mm), reducing the potential risk for fibrosis and stricture formation [2, 3], and has emerged as a promising alternative treatment [1]. According to Rustagi et al [1], who published the largest series of patients managed by RFA ( n = 39), this technique showed 96% improvement of the endoscopic severity score, 100% efficacy in stopping bleeding, and 92% of blood transfusion discontinuation, with no major complications [1].…”
mentioning
confidence: 99%